Corticobasal Ganglionic Degeneration and Progressive Supranuclear Palsy Presenting with Cognitive Decline - Bergeron, Catherine (Brain Pathol, 2006)
Corticobasal ganglionic degeneration (CBGD) and progressive supranuclear palsy (PSP) were originally described in the sixties as predominantly motor syndromes. Over the years, the detailed study of additional cases of CBGD has shown that it is a distinctive histological entity which can often present as dementia or aphasia. Although some pathological features of CBGD overlap with those of other forms of non‐Alzheimer non‐Lewy body dementia, the distribution and relative number of these abnormalities and the distinctive pattern of tau immunodeposits allows the distinction of CBGD from Pick's disease and fronto‐temporal dementia. In contrast, PSP only rarely presents with prominent dementia or behavioral changes. In these unusual PSP cases, care must be taken to exclude the diagnoses of CBGD and familial tangle‐only dementia.